2020
DOI: 10.1186/s42155-020-00107-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of uterine artery embolization with gelatin sponge for retained products of conception with bleeding and future pregnancy outcomes

Abstract: Background: Retained products of conception (RPOC) with hemorrhage need intervention when RPOC persist and remain symptomatic. The safety and efficacy of uterine artery embolization (UAE) for RPOC using gelatin sponge (GS) alone, and fertility after UAE for RPOC remain unknown. The purpose of this study is to retrospectively investigate the efficacy of UAE for RPOC with bleeding and future pregnancy outcomes. Methods: Between 2007 and 2016, 14 patients (mean age, 33 years old) diagnosed as RPOC with bleeding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…A previous retrospective study reported that the selective UAE is effective, without incidents or post-embolization complications, with a 74.2% (23/31) success rate in the primary UAE, and a combined success rate of 87.1% (27/31) in the primary and second UAE [ 12 ]. Another report showed that the technical and clinical success rate of UAE using a gelatin sponge for RPOC with hemorrhage was achieved without major complications in 93 and 100% of such cases, respectively [ 13 ]. These suggest that UAE may be useful for RPOC with marked vascularity, AVM, or EMV for preventing the risk of hemorrhage related to the surgical removal of the mass with methods such as curettage or operative hysteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study reported that the selective UAE is effective, without incidents or post-embolization complications, with a 74.2% (23/31) success rate in the primary UAE, and a combined success rate of 87.1% (27/31) in the primary and second UAE [ 12 ]. Another report showed that the technical and clinical success rate of UAE using a gelatin sponge for RPOC with hemorrhage was achieved without major complications in 93 and 100% of such cases, respectively [ 13 ]. These suggest that UAE may be useful for RPOC with marked vascularity, AVM, or EMV for preventing the risk of hemorrhage related to the surgical removal of the mass with methods such as curettage or operative hysteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few reports have mentioned angiographic features of retained placenta in affected patients [5][6][7]. In those reports, angiographic features of retained placenta have included tortuous dilated uterine artery owing into a sac-like structure, intrauterine vascular lesion with or without arteriovenous (AV) shunt, focal contrast blush, and pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Bazeries et al [5] reported that TAE technical and primary clinical successes, using mainly microspheres (size: 700-1200 µm), were achieved in 90.3% (27/31) and 74.2% (23/31) of their patients. Kimura et al [7] reported higher rates of TAE technical and clinical success using GS (93%, 13/14; 100%, 14/14). NBCA embolization of retained placenta increta was described in a case report; complete occlusion and cure was achieved with single embolization [16].…”
Section: Clinical Outcomementioning
confidence: 99%
“…Studies have shown that up to 18% of retained products of conception have marked vascularity, resulting in increased risk of hemorrhage during surgical intervention (13). Some institutions use uterine artery embolization as an adjunct in the management of retained products of conception (14) or following prolonged post-partum hemorrhage when management with conservative measures has failed (15). Iatrogenic injury may also occur at the site of vascular access or bypass anastomosis, with pseudoaneurysms being reported as a complication of 1.4-4% of arterial anastomoses (Figure 3) (16).…”
Section: Iatrogenic Injurymentioning
confidence: 99%